A Dutch Republican Baroque Theatricality, Dramatization, Moment, and Event - Korsten, Frans-Willem (Amsterdam Studies in the Dutch Golden Age, 2017)
In the Dutch Republic in the Baroque era, two aesthetic formal modes, theater and drama, were dynamically related to two political concepts, event and moment. The Dutch version of the Baroque is characterized by a fascination with this world regarded as one possibility out of a plurality of potential worlds. It is this fascination that explains the coincidence in the Dutch Republic, strange at first sight, of Baroque exuberance, irregularity, paradox, and vertigo with scientific rigor, regularity, mathematical logic, and rational distance. In giving a new historical perspective on the Baroque as a specifically Dutch republican one, this study also offers a new and systematic approach to the interactions among the notions of theatricality, dramatization, moment, and event.